Inactivation of monazomycin-induced voltage-dependent conductance in thin lipid membranes. I. Inactivation produced by long chain quaternary ammonium ions (The Rockefeller University Press, 1976)
The voltage-dependent conductance induced in thin lipid membranes by monazomycin undergoes inactivation upon the introduction of quaternary ammonium ions (QA) having a long alkyl chain (e.g. dodecyltrimethylammonium [C12]) to the side containing monazomycin. That is, in response to a step of voltage the conductance rises to a peak and then falls to a much lower steady-state value. We demonstrate that the basis of this phenomenon is the ability of QA to pass through the stimulated membrane and bind to the opposite surface. As a consequence, the surface potential on that side becomes more positive, thus reducing the voltage across the membrane proper and turning off the monazomycin-induced conductance. Because the flux of QA through the membrane increases linearly with conductance, we believe that these ions pass through the monazomycin channels. QA permeability increases with alkyl chain length; remarkably, in spite of its much larger size, C12 is about 150 times more permeant than K+. It appears, therefore, that there is a hydrophobic region of the cahnnel that favors the alkyl chain; we propose that this region is formed by the hydrophobic faces of the monazomycin channels in lipid bilayers to QA inactivation of potassium channels in the squid giant azon, and suggest that there may be a common structural feature for the two channels. It is possible that some of the inactivation phenomena in excitable cells may arise from local field changes not measurable by the recording electrodes.